Etnobotânica de plantas com atividade anti-inflamatórias: formas de preparo e usos nas comunidades Rios Doce e Prata, Abaetetuba-Pará - LEAL, Joelson Balieiro (2019)
In the Amazon the use of medicinal plants is strictly linked to the miscegenation of the cultures, customs and values that are passed on between generations. In this context, an ethnobotanical study of the medicinal plants used by residents of the Rios Doce and Prata communities with anti-inflammatory potential was carried out in the city of Abaetetuba, Pará. The methodology was selected using the "snowball" methodology. This research consisted of 35 participants, 31 of whom were female and four were male, all of them literate, over 30 years of age. 31 species were collected and identified, included in 25 families and 25 genera. The phytopharmacopoeia of these communities is of great importance to the population, since the various forms of preparation and use of these home remedies are intended to meet the demands of these residents, mainly in relation to inflammatory processes.